2021
DOI: 10.3390/w13141935
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Integrating SWAT Model into a Multi-Criteria Decision Analysis towards Reliable Rainwater Harvesting Systems

Abstract: Rainwater harvesting (RWH) has been recognized as one of the most reliable and efficient methods for water supply, especially in arid and semi-arid regions (ASARs) facing freshwater scarcity. Nevertheless, due to the inherent uncertainty of input data and subjectivity involved in the selection of influential parameters, the identification of RWH potential areas is a challenging procedure. In this study, two approaches for locating potential RWH sites were implemented. In the first approach, a frequently-used m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…Year Applied Techniques Country [47] 2022 WLC, RS, and GIS Australia [48] 2021 AHP and GIS Morocco [49] 2021 BO, WLC, and GIS Iraq [50] 2017 AHP, Fuzzy-AHP, ROM, VI, BO, RS, SWAT, and GIS Iraq [51] 2021 WLC, BO, RS, and GIS Iraq [30] 2017 FL, AHP, WLC, and GIS Iraq [4] 2020 AHP, WSM, RS, and GIS Iraq [2] 2019 WLC, AHP, RS, and GIS Iraq [31] 2019 AHP, FL, RS, and GIS Iraq [52] 2017 WLC, BO, and GIS Jordan [53] 2016 AHP, WLC, BO, and GIS Jordan [54] 2022 AHP, WLC, BO, RS, and GIS Yemen [55] 2014 AHP, FIM, BO, WLC, and GIS Pakistan [33] 2020 AHP, RS, and GIS Pakistan [29] 2019 AHP, ML, GIS, and RS UAE [56] 2019 AHP, SSS, and GIS Iran [57] 2021 AHP, WLC, and GIS Iran [23] 2018 AHP, TOPSIS, and GIS Iran [44] 2021 AHP, WLC, SWAT, RS, and GIS Iran [20] 2020 BWM, FL, AHP, WOP, BO, and GIS Iran [8] 2022 AHP, RS, SWAT, RUSLE, and GIS Rwanda [58] 2021 AHP, RS, and GIS MOZ The torrential rainfall and subsequent floods of spring 2019 that hit Iraq and neighboring countries [56,59] raised water levels in the Tigris River and its tributaries (Figure 1a). Consequently, water management features such as Dukan Reservoir (DR) reached its maximum safe storage capacity.…”
Section: Referencementioning
confidence: 99%
See 3 more Smart Citations
“…Year Applied Techniques Country [47] 2022 WLC, RS, and GIS Australia [48] 2021 AHP and GIS Morocco [49] 2021 BO, WLC, and GIS Iraq [50] 2017 AHP, Fuzzy-AHP, ROM, VI, BO, RS, SWAT, and GIS Iraq [51] 2021 WLC, BO, RS, and GIS Iraq [30] 2017 FL, AHP, WLC, and GIS Iraq [4] 2020 AHP, WSM, RS, and GIS Iraq [2] 2019 WLC, AHP, RS, and GIS Iraq [31] 2019 AHP, FL, RS, and GIS Iraq [52] 2017 WLC, BO, and GIS Jordan [53] 2016 AHP, WLC, BO, and GIS Jordan [54] 2022 AHP, WLC, BO, RS, and GIS Yemen [55] 2014 AHP, FIM, BO, WLC, and GIS Pakistan [33] 2020 AHP, RS, and GIS Pakistan [29] 2019 AHP, ML, GIS, and RS UAE [56] 2019 AHP, SSS, and GIS Iran [57] 2021 AHP, WLC, and GIS Iran [23] 2018 AHP, TOPSIS, and GIS Iran [44] 2021 AHP, WLC, SWAT, RS, and GIS Iran [20] 2020 BWM, FL, AHP, WOP, BO, and GIS Iran [8] 2022 AHP, RS, SWAT, RUSLE, and GIS Rwanda [58] 2021 AHP, RS, and GIS MOZ The torrential rainfall and subsequent floods of spring 2019 that hit Iraq and neighboring countries [56,59] raised water levels in the Tigris River and its tributaries (Figure 1a). Consequently, water management features such as Dukan Reservoir (DR) reached its maximum safe storage capacity.…”
Section: Referencementioning
confidence: 99%
“…Many insightful studies have revealed that integrating the WLC and AHP approaches with GIS is an effective and competent RH suitability technique [2,44,54]. The WLC and AHP models have been utilized to determine suitable RH locations by identifying the weights of various criteria and their sub-criteria [4,47,48,53].…”
Section: Generation Of Runoff Harvesting Suitability Mapsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study evaluates the rainwater harvesting system using the SWAT model and MCDA in Iran (Doulabian et al 2021).…”
Section: Downstream Water Resource Developmentmentioning
confidence: 99%